Pengaruh Capital Intensity Ratio (CIR), Debt to Asset Ratio (DAR), dan Kompensasi Kerugian Fiskal terhadap Effective Tax Rate (ETR) pada Perusahaan Sektor Properti yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Yudhistira, Gabrielle; Lubis, Nurul Izzah; Masyitah, Emi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to test and analyze the effect of the Capital Intensity Ratio, Debt to Asset Ratio, and Tax Loss Carryforward on the Effective Tax Rate in state-owned enterprises listed in the property sector for the period 2019–2023. This study uses a quantitative research approach to examine the causal relationship between independent variables and the dependent variable through statistical analysis. The population of this study consists of  companies in the property sector listed on the Indonesia Stock Exchange during 2019-2023. The sampling technique applied was purposive sampling, resulting in 20 companies selected. The data used are secondary data obtained from the companies’ annual financial statements. Data analysis was conducted using multiple linear regression analysis. Prior to hypothesis testing, classical assumption tests were performed to ensure the validity of the regression model. Hypothesis testing was carried out using t-tests to examine the partial effects of each independent variable, F-tests to assess the simultaneous effects, and the coefficient of determination to measure the model’s explanatory power. All analyses were processed using SPSS version 25. The results indicate that the Capital Intensity Ratio has a negative effect on the Effective Tax Rate, the Debt to Asset Ratio also has a negative effect on the Effective Tax Rate, while Tax Loss Carryforward has a positive effect on the Effective Tax Rate. Simultaneously, the results show that the Capital Intensity Ratio, Debt to Asset Ratio, and Tax Loss Carryforward have a significant effect on the Effective Tax Rate.